Hollywood's Italian American filmmakers : Capra, Scorsese, Savoca, Coppola, and Tarantino - Cavallero, Jonathan J. (University of Illinois Press, 2011)
"[This book] explores the different ways in which Italian American directors from the 1920s to the present have responded to their ethnicity. While some directors have used film to declare their ethnic roots and create an Italian American 'imagined community, ' others have ignored or even denied their background ... Cavallero's exploration of the films of Capra, Scorsese, Savoca, Coppola, and Tarantino demonstrates how immigrant Italians fought prejudice, how later generations positioned themselves in relation to their predecessors, and how the American cinema, usually seen as a cultural instituion that works to assimlate, has also served as a forum where assimilation was resisted."--Book cover